2020
DOI: 10.3389/fnins.2020.00005
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke During the Early Postnatal Period of Mice Interferes With Brain 18 F-FDG Uptake From Infancy to Early Adulthood – A Longitudinal Study

Abstract: Exposure to environmental tobacco smoke (ETS) is associated with high morbidity and mortality, mainly in childhood. Our aim was to evaluate the effects of postnatal ETS exposure in the brain 2-deoxy-2-[ 18 F]-fluoro-D-glucose (18 F-FDG) uptake of mice by positron emission tomography (PET) neuroimaging in a longitudinal study. C57BL/6J mice were exposed to ETS that was generated from 3R4F cigarettes from postnatal day 3 (P3) to P14. PET analyses were performed in male and female mice during infancy (P15), adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The exposure biomarkers found in this study are consistent with those reported in previous studies of our research group ( Lobo Torres et al, 2012 ; Torres et al, 2015a , 2015b ; Torres et al, 2019a ; Torres et al, 2019b ; Torres et al, 2020 ), as well as with those of other studies ( Mello et al, 2001 ). Due to the rapid metabolization of nicotine, cotinine and 3-hydroxycotinine were used as biological biomarkers of ETS exposure ( Man et al, 2006 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The exposure biomarkers found in this study are consistent with those reported in previous studies of our research group ( Lobo Torres et al, 2012 ; Torres et al, 2015a , 2015b ; Torres et al, 2019a ; Torres et al, 2019b ; Torres et al, 2020 ), as well as with those of other studies ( Mello et al, 2001 ). Due to the rapid metabolization of nicotine, cotinine and 3-hydroxycotinine were used as biological biomarkers of ETS exposure ( Man et al, 2006 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, early postnatal exposure to ETS impairs myelination, learning, and memory, besides decreasing brain-derived neurotrophic factor (BDNF) and synaptic proteins levels ( Toledo-Rodriguez et al, 2010 ; Torres et al, 2015a , b ). In a study conducted by Torres et al (2020) , the authors found that ETS exposure during the early postnatal period decreased 18 fluorine-fluorodeoxyglucose ( 18 F-FDG) uptake, a marker of brain metabolic activity, in several brain areas of males and females from late infancy to early adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, one caveat of these studies is that a causal relationship can’t be drawn solely based on human population studies since the risk factors of developing MS later in life is multifaceted and may not be simply due to early-life ETS exposure. New findings in animal studies are emerging strengthening the idea that exposure to tobacco smoke in a critical period interferes with brain development of mice from late infancy to early adulthood (Wu et al, 2009, 2012; Torres et al, 2019, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Exposure to tobacco smoke is also associated with irritability (Froggatt et al, 2020), attention deficit hyperactivity disorder (Kovess et al, 2015), and sudden infant death syndrome (Alm et al, 2006). In rodents, exposure to tobacco smoke during the early postnatal period induces learning and memory impairment (Torres, Annoni, et al, 2015) and inhibits the expression of genes required for myelin formation and maintenance, thus contributing to white matter degeneration (Yu et al, 2016); decreases brain 2‐deoxy‐2‐[ 18 F]‐fluoro‐ d ‐glucose ( 18 F‐FDG) metabolism in hippocampus (Torres et al, 2020); increases the preference of adult mice for the drug in two‐bottle‐choice test (Romoli et al, 2019); and affects lung maturation (Blaskovic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%